Globalization, Uncertainty and Youth in Society: The Losers in a Globalizing World - Blossfeld, Hans-Peter; Klijzing, Erik; Mills, Melinda; Kurz, Karin (Routledge, 2006)
Examining how youths in fourteen industrialized societies make the transition to adulthood in an era of globalization and uncertainty, this book features an array of international contributions, and includes case studies and original empirical data.
Keywords: jeunesse